Efektivitas Penerapan Problem-Based-Learning Untuk Meningkatkan Motivasi Belajar, Kreativitas dan Penguasaan Konsep Siswa [Efectivity of Problem-Based-Learning Implementation to Improve Student's Learning Motivation, Creativity and Mastery of the Concept] - Jessica Ayudia (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2021)
This study aims to determine the implementation of Problem-Based Learning in Mathematics, as well as determine the increase motivation, creativity and mastery of the concept of student learning outcomes through the implementation of Problem-Based Learning in Class 5A SDS Lentera Harapan Curug. Subjects were students in class 5A in SDS Lentera Harapan by the number of students by 36 students consisting of 19 female students and 17 male students. The study was conducted using a model of classroom action research conducted three cycles, each cycle consisting of four stages: planning, action, observation and reflection. The data collection is done by using observation observer, student test results, and additional instruments such as interview sheets, sheet learning motivation and creativity sheet. The results showed that the Problem Based Learning Math can help the learning process. Stages Problem Based-Learning helps students to understand the issues in the matter and the process to get a response. The development is seen in students' motivation in cycle 1 to cycle 3 to increase. Creativity and mastery of the concept of student learning outcomes have not been able to increase in cycle 1 to cycle 3 with entirely due process of problem-based learning-Learning newly conceived and performed by students. Math learning outcome of the results of the summative second cycle in which more than 70% the number of students successfully meet the KKM.